Effectiveness of a Positive Deviance–Based Educational Intervention on Children’s Self-Esteem for Bullying Prevention: A Quasi-Experimental Study - Wahyuni, Retno; Marliani, Marliani; Lusiatun, Lusiatun; Japar, Abdul; Pangaribuan, Ingka Kristina; Manurung, Herna Rinayanti; Adethia, Kismiasih; Fathahilah, Bunga Dwi; Sinaga, Intan Putri; Dalimunthe, Juwita Rantika (Chakra Brahmanda Lentera Institute, 2026)
Background: Bullying is a critical school issue rooted in low self-esteem, which serves as a major vulnerability factor for children. This study aims to analyze the role of Positive Deviance (PD) education in improving children’s self-esteem as a bullying prevention strategy. Methods: A quantitative quasi-experimental pretest–posttest control group design was employed. The population consisted of grade VI students at SD Negeri 101893 Bangun Rejo, with a total sample of 58 students, divided into an experimental (n=29) and a control (n=29) group. Sampling involved identifying